2009
DOI: 10.1007/s00424-009-0693-8
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis identifies matrix metalloproteinases (MMPs) as key genes whose expression is up-regulated in human adipocytes by macrophage-conditioned medium

Abstract: White adipose tissue exhibits inflammation as tissue mass expands in obesity, involving macrophage infiltration and a direct inflammatory response by adipocytes. DNA microarrays and conditioned medium have been used to examine the effects of macrophages on global gene expression in human adipocytes. SGBS adipocytes, differentiated in culture, were treated with macrophage-conditioned medium (U937 cells) for 4 or 24 h; control cells received unconditioned medium. Agilent arrays comprising 44,000 probes were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 52 publications
10
97
0
Order By: Relevance
“…In agreement with our results, an interesting study performed on the adipose tissue of mice reported the presence of several members of MMPs and TIMPs, except MMP-8 [26]. A microarray study showed that while various MMP family members were strongly upregulated in adipocytes in a culture-conditioned medium, MMP-8 upregulation was not observed [27]. These data support our findings and suggest that adipose tissue probably does not synthesize MMP-8 in amounts sufficient to interfere with MMP-8 systemic levels.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our results, an interesting study performed on the adipose tissue of mice reported the presence of several members of MMPs and TIMPs, except MMP-8 [26]. A microarray study showed that while various MMP family members were strongly upregulated in adipocytes in a culture-conditioned medium, MMP-8 upregulation was not observed [27]. These data support our findings and suggest that adipose tissue probably does not synthesize MMP-8 in amounts sufficient to interfere with MMP-8 systemic levels.…”
Section: Discussionsupporting
confidence: 92%
“…During AT expansion, the ECM actively remodels to accommodate the growth. We and others have demonstrated that several ECM components are upregulated during fat mass expansion in states of obesity (102,103). AT fibrosis, with its associated reduced plasticity, is therefore a key hallmark of the metabolically dysfunctional AT.…”
Section: Angiogenesis a Rate-limiting Step For At Expansion And Remomentioning
confidence: 89%
“…MMP9 and PM20D1 are metalloproteinases. MMPs (including MMP9) are known to be upregulated in human adipocytes, 58 and have been associated with obesity in rodent models. 59,60 PRKG1, a guanosine 3 0 ,5 0 -monophosphate (cGMP)-dependent protein kinase is important in regulating foraging behavior, food acquisition and energy balance.…”
Section: Epigenetic Factors In Obesitymentioning
confidence: 99%